THE INFLUENCE OF USING CODI ON STUDENT’S MOTIVATION IN READING - Ningrum, Saraswati Eko; Fauziati, Endang; Prastiwi, Yeny (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Students' reading motivation is likely low due to internal and external factors. The internal factors, for example, are intelligence, age, gender, reading ability, attitudes, and psychological needs. The external factors include the theme, level of reading difficulty, and the type of reading. This research was conducted to know whether the use of Content Differentiated Instructions (CoDI) in teaching could affect students' motivation in reading, especially descriptive text. This kind of text was chosen because it is the simplest text among five other kinds of text that are given to beginner-level students, in this case, students of junior high school. The researcher tried to find out whether the implementation of CoDI could affect the students’ motivation in reading. In this study, the researcher used a qualitative method. The data used were in the form of answers or student responses in the form of questionnaires. The result was that using CoDI affects the students’ motivation in reading descriptive text.